Pengaruh Brand Awareness, Perceived Quality Dan Brand Trust Terhadap Customer Loyalty Produk Tolak Angin - Patricia Simon dan Miharni Tjokrosaputro (Universitas Tarumanagara, 2019)
This research was attempted to explore what factors are contributing to customer loyalty of pharmaceutical and herbal product in Indonesia. Author used Tolak Angin brand as OTC drug model. Questionnaires method was used in this research. Data were analyzed using SPSS 24.0 by using data of 231 respondents who consumed any Tolak Angin products within 6 months. The result of the research shows that brand awareness and brand trust do partially have positive impact on customer loyalty. However, perceived quality partially doesn’t have positive impact on customer loyalty. Furthermore, brand awareness, perceived quality and brand trust simultaneously do have positive impact on customer loyalty. The research provides insight to academics and pharmaceutical and traditional medicine company about how to manage customer loyalty of pharmaceutical and herbal product in Indonesia